BMSC-EVs regulate Th17 cell differentiation in UC via H3K27me3. (February 2020) - Chen, Qianyun; Duan, Xueyun; Xu, Meng; Fan, Heng; Dong, Yalan; Wu, Hui; Zhang, Man; Liu, Yujin; Nan, Zhen; Deng, Shuangjiao; Liu, Xingxing
Highlights: BMSC-EVs can alleviate UC. BMSC-EVs can inhibit the differentiation and function of Th17 cells in UC. BMSC-EVs may restrain the differentiation of UC Th17 cells by regulating histone H3K27me3. Abstract: In our previous studies, we found that extracellular vesicles in mesenchymal stem cells can alleviate ulcerative colitis. In view of the fact that extracellular vesicles have the same immunomodulatory effects as their maternal cells and considering the important role of Th17 cells in the pathogenesis of ulcerative colitis, we aimed to investigate whether extracellular vesicles from mesenchymal stem cells can affect the differentiation of Th17 cells in ulcerative colitis. Histone H3K27me3 can regulate the expression of Th17 cell-related genes. We focused on determining whether the effect of extracellular vesicles on Th17 cells in ulcerative colitis is related to H3K27me3. For our experiments, we used low, medium and high doses of extracellular vesicles from mesenchymal stem cells to interfere with TNBS-induced colitis in rats and then evaluated the alleviation of inflammation and observed the impact of the extracellular vesicles on the differentiation of Th17 cells in ulcerative colitis. In addition, we detected the levels of histone H3K27me3 and the expression of its upstream methyltransferase and demethylase in the colon tissues of each group. Our data showed that extracellular vesicles from bone marrow mesenchymal stem cells can inhibit the abnormal differentiation of Th17 cells in ulcerative colitis, and the content of histone H3K27me3 was also changed accordingly. Our study suggests that extracellular vesicles from mesenchymal stem cells could inhibit the differentiation of Th17 cells in ulcerative colitis by regulating H3K27me3. This study reveals that H3K27me3 is an important target for inflammatory immune diseases associated with abnormal Th17 cell differentiation and indicates that mesenchymal stem cell extracellular vesicles are promising agents for the treatment of ulcerative colitis.